PELATIHAN PEMBUATAN BIBIT PISANG BEBAS PENYAKIT LAYU DAN PEMUPUKAN BERIMBANG TANAMAN KAKAO DI DESA BAJRA KECAMATAN SELEMADEG TABANAN - A.A.N. Supadma; D.M. Arthagama; I M. Adnyana; I N. Puja; M. Dana; I M. Mega (Buletin Udayana Mengabdi, 2016)
Cultivation of banana plant at Dusun Menunggul, Desa Bajra, Kecamatan Selemadeg, Tabanan regency,were relatively non intensified. Famers did not know plant cultivation, exact fertilization dosage, banana andcacao deseases, and banana seedling free deseases (free Pseudomonas solanacearum and Fusariumoxysporum). In this activity the community services tems transferred to the famers some informationstechnology about cultivation of banana plant, soil fertility, fertilization for banana, pest of cacao plant anddemonstration about application Biota L and Persada for seedling banana plant, application Diamond IntresGrow petiside for pest of fruit cacao. The result of this short course conducted in Dusun Menunggul on 23Agustus 2015 with 45 attendants was ecxiting because most farmers were interested in the course substances and materials training, they understand and be able how to treat and apply Biota L and Persada for seedlingof banana plant.